A Free Irresponsible Press: Wikileaks and the Battle over the Soul of the Networked Fourth Estate - Benkler, Yochai (Politik, 2012)
The article tells the story about how Wikileaks emerged and was welcomed as a part of the fourth estate in 2006 and later, especially in 2010, was subject of a multi-system attack by both public and private actors. Wikileaks is part of the new, networked fourth estate, which is likely to combine elements of both traditional and novel forms of news media. e networked fourth estate is needlessly attacked by traditional media, but there is no reason to think that the latter is more professional and responsible than the former. e future of the fourth estate is likely a new model of cooperation between traditional and networked models, but the transition to this new model will likely be anything but smooth.